Knowledge and Practices of Patients Regarding Diabetes Self-Management: A Mixed Method Approach: Knowledge and Practices Regarding Diabetes Self-Management - ul-Islam, Noor; Ali Shah, Bakhtyar; Muhammad, Dildar; Ajmal, Hina; Karim, Shakila (Pakistan Journal of Health Sciences, 2023)
Diabetes Mellitus is a major source of death globally and has shaken middle-income and low-income countries including Pakistan. Objective: To determine diabetes knowledge, and explore the patient’s experiences of type-ii diabetes along with its self-management. Methods: A mixed-method design was used to carry out this study at a tertiary care hospital in KP Pakistan from April to September 2021. Information on patients’ demographic characteristics, diabetes knowledge, and diabetes self-practices, patients’ lived experiences of diabetes self-practices, and barriers to self-care activities were collected. Data were collected through a structured questionnaire and in-depth (IDIs) interviews for measuring diabetes knowledge, and its management. Results: Out of 215 recruited participants, the majority 90% had inadequate knowledge (score=0-4). 3.2% (n=07) had average knowledge (score=5-8) of diabetes, and its self-management. 60% of the participants were from the age group 50-59 years. 70% (n=151) of participants were from poor socioeconomic classes. The results showed an association between illiteracy, poverty, diabetes knowledge, and self-management (p-Value 0.001). The qualitative results expressed that the illiterate and low socioeconomic participants had inadequate diabetes self-management practices. Conclusions: The study inferred that the participants, who had inadequate knowledge about type-II diabetes and its management, were having poor self-care practices of diabetes.